Democracy and growth in divided societies: A health-inequality trap? - Powell-Jackson, T; Basu, S; Balabanova, D; McKee, M; Stuckler, D (2011)
Despite a tremendous increase in financial resources, many countries are not on track to achieve the child and maternal mortality targets set out in the Millennium Development Goals 4 and 5. It is commonly argued that two main social factors - improved democratic governance and aggregate income - will ultimately lead to progress in reducing child and maternal mortality. However, these two factors alone may be insufficient to achieve progress in settings where there is a high level of social division. To test the effects of growth and democratisation, and their interaction with social inequalities, we regressed data on child and maternal mortality rates for 192 countries against internationally used indexes of income, democracy, and population inequality (including income, ethnic, linguistic, and religious divisions) covering the period 1970-2007. We found that a higher degree of social division, especially ethnic and linguistic fractionalisation, was significantly associated with greater child and maternal mortality rates. We further found that, even in democratic states, greater social division was associated with lower overall population access to healthcare and lesser expansion of health system infrastructure. Perversely, while greater democratisation and aggregate income were associated with reduced maternal and child mortality overall, in regions with high levels of ethnic fragmentation the health benefits of democratisation and rising income were undermined and, at high levels of inequality reversed, so that democracy and growth were adversely related to child and maternal mortality. These findings are consistent with literature suggesting that high degrees of social division in the context of democratisation can strengthen the power of dominant elite and ethnic groups in political decision-making, resulting in health and welfare policies that deprive minority groups (a health-inequality trap). Thus, we show that improving economic growth and democratic governance are insufficient to achieve child and maternal health targets in communities with high levels of persistent social inequality. To reduce child and maternal mortality in highly divided societies, it will be necessary not only to increase growth and promote democratic elections, but also empower disenfranchised communities.